Efektivitas Media Pembelajaran Quizizz terhadap Keaktifan Belajar PAI Kelas XII SMAN 1 Lareh Sago Halaban - Desya, Ratih Sukma; Wirdati, Wirdati (YASIN, 2023)
The use of learning media is a learning strategy that must be mastered by teachers, especially interactive learning media. But in reality there are still many teachers who have not mastered interactive learning media so that it has an impact on student learning activities such as learning activeness. The research method is quantitative experiment with questionnaire distribution techniques on a sample of 32 respondents, data analysis techniques using the help of the SPPS 26 program. The results of the research on the T test show that 0.001 <0.05 which means Ho is rejected and Ha is accepted. Then the effectiveness test shows that the value of R < 1 (0.72) < 1. Based on the results of these tests, it can be concluded that Quizizz learning media is effective in increasing the activeness of PAI learning class XII at SMAN 1 Lareh Sago Halaban.